Hepta‐nuclear Zinc Tungstophosphate Nano‐cluster [Zn7(H2O)2(OH)2P2W25O94]16−: Synthesis, Characterization and its Catalytic Application in Alcohol Oxidation. Issue 3 (17th January 2023) - Das, Vivek; Hussain, Firasat
Abstract: A new hepta‐nuclear Zinc tungstophosphate nano‐cluster of formula K14 [Zn7 (H2 O)2 (OH)2 P2 W25 O94 ]Zn(H2 O)4  ⋅ 35H2 O (1 a ) was synthesized under environment‐friendly conditions in a one‐pot reaction procedure. The isolated crystalline compound was synthesized by reacting Zn(NO3 )2  ⋅ 6H2 O with the potassium salt of tungstophosphate precursor, K14 [P2 W19 O69 (H2 O)] ⋅ 24H2 O in the presence of Ce(NO3 )3  ⋅ 6H2 O in a solution of potassium chloride. The synthesized compound was characterized by instrumentation techniques such as fourier transform infrared (FT‐IR) spectroscopy, single crystal X‐ray diffraction (SC‐XRD), 31 P nuclear magnetic resonance (NMR) spectroscopy, thermogravimetric analysis (TGA), powder X‐ray diffraction (P‐XRD) and energy dispersive X‐ray (EDX) spectroscopy.The compound also shows a good catalytic activity for the oxidation of alcohols. Abstract : A new hepta‐nuclear Zinc substituted tungstophosphate nano‐cluster [Zn7 (H2 O)2 (OH)2 P2 W25 O94 ] 16− has been synthesized via one‐pot environment friendly procedure and characterized by various analytical techniques. The complex shows good catalytic activity for the alcohol oxidation.